Influence of hospital and clinician workload on survival from colorectal cancer: cohort study - Kee, F (BMJ Group, 1999)
OBJECTIVE: To determine whether clinician or hospital caseload affects mortality from colorectal cancer. DESIGN: Cohort study of cases ascertained between 1990 and 1994 by a region-wide colorectal cancer register. OUTCOME MEASURES: Mortality within a median follow up period of 54 months after diagnosis. RESULTS: Of the 3217 new patients registered over the period, 1512 (48%) died before 31 December 1996. Strong predictors of survival both in a logistic regression (fixed follow up) and in a Cox's proportional hazards model (variable follow up) were Duke's stage, the degree of tumour differentiation, whether the liver was deemed clear of cancer by the surgeon at operation, and the type of intervention (elective or emergency and curative or palliative intent). In a multilevel model, surgeon’s caseload had no significant effect on mortality at 2 years. Hospital workload, however, had a significant impact on survival. The odds ratio for death within 2 years for cases managed in a hospital with a caseload of between 33 and 46 cases per year, 47 and 54 cases per year, and ⩾55 cases per year (compared to one with ≤23 cases per year) were respectively 1.48 (95% confidence interval 1.03 to 2.13), 1.52 (1.08 to 2.13), and 1.18 (0.83 to 1.68). CONCLUSIONS: There was no detectable caseload effect for surgeons managing colorectal cancer, but survival of patients treated in hospitals with caseloads above 33 cases per year was slightly worse than for those treated in hospitals with fewer caseloads. Imprecise measurement of clinician specific “events rates” and the lack of routinely collected case mix data present major challenges for clinical audit and governance in the years ahead.